VD_FINDINFO Réc-civile / 2015 / 23 vom 9. Juli 2015 - VD Tribunal cantonal (2015)
RÉCUSATION, EXPERT, MENACEEN GÉNÉRAL, DROIT DE GARDE | 319 let. b ch. 1 CPC (CH), 47 al. 1 let. f CPC (CH), 50 al. 2 CPC (CH), 8a al. 7 CDPJ